Teaching Techniques Applied in Senior High School for Students with Special Needs (SMALB) - puji rahayu (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2016)
Teaching English as a foreign language to students with special needs is somewhat different of those mainstream students. The teachers may face lots of difficulties and therefore, they must apply different techniques in teaching the students. The goal of this study is to figure out the techniques applied for Teaching English to students with special educational needs. This study is conducted in a Senior high school for students with special needs (SMALB) in Banjarmasin, South Kalimantan. The study is based on classroom observations and interview with the English teacher. The findings conclude that teacher applied six different techniques in teaching English as follow; (1) transcription, (2) Question and Answer, (3) Repetition Drill, (4) Reading Aloud, (5) Memorization and (6) Reading aloud.